Implementing VR Technology in POLIMAS Website - Sarina, Sariff (2003)
Nowadays the technology of Virtual Reality (VR) has been developed for many purposes and has expanded into many types for of field. One of the fields in virtual Reality is web page. Virtual Reality techology in web page enables users to immerse in the real world using 3-D images. This study proposed to integrate the Virtual Reality technology with the POLIMAS website. Methodology used to built the webpage is Waterfall methodology and Rapid Software Prototyping Methodology technique is used to develop the prototype. During the development some problems and limitation have been encountered. The problems arise have been discussed and solved in order to make the prototype more efficient. The webpage enhanced the services/facilities POLIMAS had offered to their students and to the outsiders. In this project, three virtual tour and six panoramic views have been created. This project is hoped to give benefits to POLIMAS staffs, students and administration staffs to assist their daily activities and also hope that it will give more benefits to the outsiders during their visit to POLIMAS.